Avaliação do potencial antiproliferativo, genotóxico e antimutagênico das espécies Psychotria brachypoda (Müll. Arg.) Briton e Psychotria birotula Smith & Downs (Rubiaceae) - Frescura, Viviane Dal Souto (2012)
Species of the genus Psychotria L. are used in Brazilian folk medicine as tea, however, their indiscriminate and uncontrolled can cause more harm than good to health. It is important to understand these plants, from their cellular levels to the action on living organisms, and for monitoring toxic substances allelopathic bioassays are widely used with plant species as the target organisms. This study aimed to evaluate the genotoxic, antiproliferative and antimutagenic potential of infusions of Psychotria brachypoda (Muell. Arg.) Briton and Psychotria birotula Smith & Downs on the cell cycle of Allium cepa L., in addition to analyzing the antiproliferative and genotoxic potential on the germination on seeds and cell cycle of Eruca sativa Mill. For this, dried leaves were used to prepare extracts in two concentrations for each species: 5g.L-1 and 20g.L-1, using distilled water as a negative control and glyphosate 3% as a positive control. For the study, antiproliferative on the germination (allelopathic potential) variables were analyzed: total number of germinated seeds, seedling root length, index of germination rate, and germination percentage. To evaluate the genotoxic, antiproliferative and antimutagenic potential, both for the test with A. cepa and with E. sativa were analyzed mitotic index and the number of chromosomal alterations. The extracts of P. brachypoda have no genotoxic potential, though the extracts of P. birotula possess genotoxic potential on the A. cepa cell cycle and the extracts of P. brachypoda and P. birotula showed no antimutagenic potential, no entanto, apresentaram genotoxic, and antiproliferative potential on the germination and cell cycle E. sativa.